3. EFFICIENCY OF REDUCING BRAXTON HICKS AND ADVERSE EFFECTS OF NIFEDIPINE IN TREATMENT OF PREMATURE LABOR (Vietnam Journal of Community Medicine, 2023)
Objectives: To describe the effectiveness of reducing braxton hicks and the adverse effects of nifedipine in treating premature labor. Subjects and methods: a retrospective descriptive study on 220 pregnant women who came to the emergency department of Obstetrics and Gynecology, Vinh Long Provincial General Hospital, were diagnosed with premature labor from January 1st, 2021 to December 31st, 2021. Results: The successful rate of prolongation of pregnancy ≥48 h in women with threatened preterm labor between 28 and 34 weeks treated with nifedipine was 70.5% (95% CI 66.6 – 74.0). The cumulative probability of successful treatment was more than 50% when the total treatment dose was at least 5 doses. The average length of gestational age was 21 days. The rate of pregnant women and fetuses with adverse effects of nifedipine during treatment was 6.4%, which often appeared transiently after the loading dose. Conclusion: The success rate of prolonging pregnancy in women with threatened preterm birth with nifedipine was 70.5%. The incidence of adverse effects in pregnant women and fetuses of nifedipine was usually transient after the loading dose.
Keywords: Nifedipine, premature labor, effectiveness, side effects.